Building patient capacity to participate in care during hospitalisation: a scoping review. Issue 7 (3rd July 2019) - Goodridge, Donna; McDonald, Meghan; New, Lucia; Scharf, Murray; Harrison, Elizabeth; Rotter, Thomas; Watson, Erin; Henry, Chrysanthus; Penz, Erika D
Abstract : Objectives: To map the existing literature and describe interventions aimed at building the capacity of patients to participate in care during hospitalisation by: (1) describing and categorising the aspects of care targeted by these interventions and (2) identifying the behaviour change techniques (BCTs) used in these interventions. A patient representative participated in all aspects of this project. Design: Scoping review. Data sources: MEDLINE, Embase and CINAHL (Inception −2017). Study selection: Studies reporting primary research studies on building the capacity of hospitalised adult patients to participate in care which described or included one or more structured or systematic interventions and described the outcomes for at least the key stakeholder group were included. Data extraction: Title and abstract screening and full text screening were conducted by pairs of trained reviewers. One reviewer extracted data, which were verified by a second reviewer. Interventions were classified according to seven aspects of care relevant to hospital settings. BCTs identified in the articles were assigned through consensus of three reviewers. Results: Database searches yielded a total 9899 articles, resulting in 87 articles that met the inclusion criteria. Interventions directed at building patient capacity to participate in care while hospitalised were categorised as those related to improving: patient safety (20.9%); care coordination (5.7%); effective treatment (5.7%) and/or patient-centred care using: bedside nursing handovers (5.7%); communication (29.1%); care planning (14%) or the care environment (19.8%). The majority of studies reported one or more positive outcomes from the defined intervention. Adding new elements (objects) to the environment and restructuring the social and/or physical environment were the most frequently identified BCTs. Conclusions: The majority of studies to build capacity for participation in care report one or more positive outcomes, although a more comprehensive analysis is warranted.